Effectiveness Of Isometric And Range Of Motion (Rom) Exercise Toward Elderly Muscle Strenght In Pasuruan Integrated Service Unit, Elderly Social Services In Lamongan - Nurus Safa'ah; Ika Desti Srimurayani (Biomedical Engineering, 2017)
Objective: Aging is a physiological process that will reduces the function of all organs, among other the musculoskeletal system that cause decreased muscle strenght. Under less of the muscle strenght will reduces activities and mobilization ability. Isometric and Range Of Motion (ROM) exercise is efficient alternative exercise for the elder who will begin the exercise program. This study was aimed to explain the difference of effectiveness between isometric and ROM exercise toward elderly muscle strenghtMaterial and methods: This study used to Pre Test and Post Test Design with time period approach involved 36 respondents, taken by purposive sampling. They were divided in to 2 groups; one group of 18 respondents underwent isometric exercise and the other group of 18 respondents did ROM exercise. Data were collected by checklist. Data were analyzed using Mann Whitney Test with level of significance α ≤ 0,05.Result: Based on the result of research there were 8 (44,4%) respondents who had increased muscle strength after did isometric exercise, and were 14 (77,8%) respondents who had ones with ROM exercise. The analysis result using Mann Whitney Test showed p = 0,044 it means that H0 is rejected, so there are difference of effectiveness between isometric and Range Of Motion (ROM) exercise toward elderly muscle strenght. Range Of Motion (ROM) exercise was proven more effective to increase elderly muscle strenght who have normal movement, while isometric exercise was recommended to maintain muscle strength for the elderly who get the injured extremity and contraindications to do movement.Conclusion: It can be used as a program to create healthy elderly and using optimally their time to do better things, such as doing ROM and isometric exercise.